Хочкинова болест и бременост - приказ на случај - Pivkova Veljanovska, Aleksandra; Genadieva Stavrikj, Sonja; Stojanoski, Zlate; Cadievski, Lazar; Stefanija, Adela; Chaparoska, Daniela; Cevreska, Lidija; Georgievski, Borche (Македонско лекарско друштво = Macedonian medical association/Walter de Gruyter GmbH, 2014)
The article presents a case with diagnosed Hodgkin disease (HD) during pregnancy. The aim of this case study was to present diagnostic possibilities in determining HD stage during pregnancy and therapeutic dilemmas. The incidence of HD during pregnancy is 3.2% of all cases with this malignant hematological disorder. The treatment of this disease during pregnancy depends on disease-related factors, pregnancy-related factors, as well as possible implications for fetal morbidity and mortality. The need of analysis of the nature of the disease during pregnancy indicates examination of a larger series of pregnant women with HD and the drawn conclusions affect the decision whether chemotherapy treatment should start immediately or it should be postponed for after delivery.
Hodgkin Disease and Pregnancy - A Case Report